Adaptive mechanisms driving maladaptive pain: how chronic ongoing activity in primary nociceptors can enhance evolutionary fitness after severe injury. (11th November 2019) - Walters, Edgar T.
Abstract : Chronic pain is considered maladaptive by clinicians because it provides no apparent protective or recuperative benefits. Similarly, evolutionary speculations have assumed that chronic pain represents maladaptive or evolutionarily neutral dysregulation of acute pain mechanisms. By contrast, the present hypothesis proposes that chronic pain can be driven by mechanisms that evolved to reduce increased vulnerability to attack from predators and aggressive conspecifics, which often target prey showing physical impairment after severe injury. Ongoing pain and anxiety persisting long after severe injury continue to enhance vigilance and behavioural caution, decreasing the heightened vulnerability to attack that results from motor impairment and disfigurement, thereby increasing survival and reproduction (fitness). This hypothesis is supported by evidence of animals surviving and reproducing after traumatic amputations, and by complex specializations that enable primary nociceptors to detect local and systemic signs of injury and inflammation, and to maintain low-frequency discharge that can promote ongoing pain indefinitely. Ongoing activity in nociceptors involves intricate electrophysiological and anatomical specializations, including inducible alterations in the expression of ion channels and receptors that produce persistent hyperexcitability and hypersensitivity to chemical signals of injury. Clinically maladaptive chronic pain may sometimes result from the recruitment of this powerful evolutionary adaptation to severe bodily injury. This article is part of the Theo Murphy meeting issue 'Evolution of mechanisms and behaviour important for pain'.